Pengaruh Kualitas Pelayanan, Harga dan Citra Merek Terhadap Keputusan Pembelian Buku pada Mentari Bookstore Jakarta - Indriarto, Titus; Kusdyah Rachmawati, Ike; Handoko, Yunus (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to analyze the influence of service quality, price, and brand image on consumers’ purchase decisions of books at Mentari Books Indonesia, specifically at the Puri Indah branch in Jakarta. In the context of an increasingly competitive business environment, a comprehensive understanding of the factors influencing consumer purchase decisions is crucial for companies to maintain and enhance their sales performance. The three primary factors examined in this research—service quality, price, and brand image—are considered to play a significant role in shaping consumer purchase decisions. The sample for this study consisted of customers of Mentari Bookstore in the Jakarta area. A quantitative research method was employed, using multiple linear regression analysis as the main analytical technique. The findings reveal that service quality does not have a significant effect on consumers’ purchase decisions at Mentari Bookstore Jakarta. Conversely, price has a significant effect on purchase decisions, as does brand image, which also exerts a significant influence on consumer purchasing behavior. Collectively, service quality, price, and brand image have a combined influence on purchase decisions at Mentari Bookstore Jakarta.